2018
DOI: 10.3389/fgene.2018.00190
|View full text |Cite
|
Sign up to set email alerts
|

The Public’s Awareness of and Attitude Toward Research Biobanks – A Regional German Survey

Abstract: Background: Biobanks have become an increasingly important means of biomedical research and innovation. However, they entail a variety of ethical, social and legal challenges, which need to be publicly discussed and managed collectively. A certain level of public awareness of biobank research is an important prerequisite for the public to form an opinion on the issue at hand and to be willing to participate in public engagement activities. For many countries, including Germany, recent information on the public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
3
23
2
1
Order By: Relevance
“…This is lower than in the study by Merdad et al where 73% of health science students in Saudi Arabia reported never having heard of biobanking [23]. This limited knowledge is consistent with the results of previous surveys conducted in other parts of the world [24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 86%
“…This is lower than in the study by Merdad et al where 73% of health science students in Saudi Arabia reported never having heard of biobanking [23]. This limited knowledge is consistent with the results of previous surveys conducted in other parts of the world [24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 86%
“…Our data also suggest that preferences collected during the initial consent process do not dependably predict long-term opinions of biobank participants. Studies have found that a high percentage of those approached about biobank membership have never heard of a biobank [ 31 , 32 ]. This suggests that many individuals who enroll in biobanks may be expressing preferences at the same moment in time in which they are learning what a biobank is and what their participation entails.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only 63.4% of the respondents expressed their willingness to participate. While, in some previous studies, respondents showed a more positive attitude towards donating biospecimens (64%-90%) [20,21]. The reason was we thought may due to their in-invasive collecting methods described in their article in a biobank.…”
Section: Discussionmentioning
confidence: 56%